Electronic Metal–Support Interaction Modulation of Single‐Atom Electrocatalysts for Rechargeable Zinc–Air Batteries. Issue 3 (17th January 2022) - Wu, Mingjie; Zhang, Gaixia; Wang, Weichao; Yang, Huaming; Rawach, Diane; Chen, Mengjun; Sun, Shuhui
Abstract: High‐performance oxygen electrocatalysts play a key role in the widespread application of rechargeable Zn–air batteries (ZABs). Single‐atom catalysts (SACs) with maximum atom efficiency and well‐defined active sites have been recognized as promising alternatives of the present noble‐metal‐based catalysts for oxygen reduction reaction and oxygen evolution reaction. To improve their oxygen electrocatalysis activities and reveal the structure–activity relationship, many advanced synthesis and characterization methods have been developed to study the effects of 1) coordination and electronic structure of the metal centers and 2) morphology and stability of the conductive substrates. Herein, a detailed review of the recent advances of SACs with strong electronic metal–support interaction (EMSI) for rechargeable ZABs is provided. Great emphasis was placed on the EMSI forms and design strategies. Moreover, the importance and the impact of the atomic coordinating structure and the substrates on the oxygen electrocatalytic activity and stability are highlighted. Finally, future directions and perspectives on the development of SACs are also presented. Abstract : This review explores the development of single‐atom catalysts (SACs) with a strong electronic metal–support interaction for rechargeable Zn–air batteries (ZABs). SAC design strategies and the impact of the metal atom coordination and substrate on the activity and stability are highlighted. This review serves as a framework for the rational design of SACs for high performance rechargeable ZABs.